State Supervision of Labour Legislation in the Light of Association Agreement - Zhorzholiani, Levan (Journal of Law, 2017)
Labour legislation plays the essential lrole in the life of each and every citizen and this is conditioned by the phenomenon of labour itself. The enforcement of law in this field is associated with the economic welfare of men to a certain extent, respectively, when employees and employers take full advantage of the opportunities, prescribed by labour legislation, this results in well-balanced employment relationships which are directly linked with the productivity of public and civil entities, organizations, enterprises. In certain cases, to keep the balance, it becomes necessary for the state to interfere and to introduce the state supervision of the legislation. The paper below discusses such cases and offers the justification of the importance of control over the enforcement of labour legislation both at national and international level.